#ec: Findings and implications from a quantitative content analysis of tweets about emergency contraception. (7th January 2016) - Gurman, Tilly A; Clark, Tiffany
Twitter, a popular social media, helps users around the world quickly share and receive information. The way in which Twitter frames health issues – especially controversial issues like emergency contraception (EC) – can influence public opinion. The current study analyzed all English-language EC-related tweets from March 2011 ( n  = 3535). Variables measured user characteristics (e.g. gender), content (e.g. news, humor), Twitter-specific strategy (e.g. retweet), and certain time periods (e.g. weekends). The analysis applied chi-square and regression analyses to the variables. Tweets most frequently focused on content related to news (27.27%), accessing EC (27.27%), and humor (25.63%). Among tweets that were shared, however, the most common content included humor, followed by personal/vicarious experience. Although only 5.54% of shared tweets mentioned promiscuity, this content category had the strongest odds for being shared (OR = 1.51; p  = 0.031). The tweet content with lowest odds of being shared were side effects (OR = 0.24; p  < 0.001), drug safety (OR = 0.44; p  < 0.001), and news (OR = 0.44; p  < 0.001). Tweets with the greatest odds of having been sent on a weekend sought advice (OR = 1.94; p  = 0.012), addressed personal or vicarious experience (OR = 1.91; p  < 0.001), or contained humor (OR = 1.56; p  < 0.001). Similar patterns occurred in tweets sent around St. Patrick's Day. Only a few differences were found in the ways in which male and female individuals discussed EC on Twitter. In particular, when compared to males, females mentioned birth control ( p  = 0.002), EC side effects ( p  = 0.024), and issues related to responsibility ( p  = 0.003) more often than expected. Study findings offer timely and practical suggestions for public health professionals wanting to communicate about EC via Twitter.